Novel insight on the impact of enzymatic addition on organic loading rate in anaerobic digestion - Villa, Raffaella; Jantova-Patel, Jana; Bajón Fernández, Yadira (Springer, 2022)
Addition of enzymes to anaerobic digesters (ADs) has been reported as beneficial to the hydrolytic step of the process. Additional benefits have been described for bioadded reactors such as improved dewatering and lower energy requirements. This work aimed to assess the long-term and unaccounted effects of enzymatic addition on sludge digestion. Enzymes’ impacts were tested using different addition modes (bulk or gradual addition) and during operational changes on reactors operated for 295 days. Enzyme added in bulk, generated a 14% increase in biogas production (144 ml/gVSadded) compared to control (126 ml/gVSadded), whereas the same amount of enzyme added gradually produced a 10% increase (139 ml/gVSadded). These values however, where higher when the OLR was increase from 3 to 5.5 kg VS/(m3 day): 257, 212 and 149 ml/gVSadded for the enzyme added in bulk, the enzyme added gradually and the control respectively. Specific biogas yields (SBY), higher in bioadded reactors, were significantly different between control reactors and those reactors dosed in bulk. Furthermore, following OLR increase, the mode of enzyme addition resulted in different increases in gas production rate (GPR) when the enzyme was added in one dose compared to control and to a gradual addition, 121%, 32% and 93% respectively. These results offer a new hypothesis on the impact of bioadditions to AD during changing operational conditions, suggesting a potential stabilising effect of the enzymes in continuous systems.
Keywords: Direct addition; Biogas specific yields; Biogas production rate; Addition mode; Cellulases; Enzyme